Contribution of predictors of knowledge, perceptions, attitudes and behavior of standard 6 pupils towards environment - Abdullah, Nurul Hidayah Liew; Shafii, Haryati; Seow, Ta Wee (Universiti Pendidikan Sultan Idris, 2018)
This study was conducted to identify predictors of knowledge, perceptions, attitudes and behaviors of the environment towards predetermined variables. A questionnaire was employed to obtain information and data from 685 respondents consisting of standard 6 pupils in Kulaijaya, Johor. The predictor variables applied in this study are the pupils' knowledge, perception and attitudes towards the environment while the dependent variable is pupils’ behavior towards the environment. Statistical Package for the Social Sciences (SPSS) version 20.0 has been used to analyze the data obtained. Multiple regression analysis was applied to determine forecasters against the specified variables. The findings show that a perception is dominan predictor to pupils’ behavior toward environment. In conclusion, not all predictor variables mentioned in this study contribute either directly or indirectly to the predetermined variables of the natural environment. Therefore, more effective measures need to be taken to ensure environmental sustainability.